The curious case of Charles Darwin’s frog, Rana charlesdarwini Das, 1998: Phylogenetic position and generic placement, with taxonomic insights on other minervaryan frogs (Dicroglossidae: Minervarya) in the Andaman and Nicobar Archipelago. - Indraneil, Das; Sonali, Garg; Sivaperuman, Chandrakasan; Gokulakrishnan, G.; Gopika, C.; Biju, S. D. (Senckenberg Society for Nature Research, Germany, 2022)
Since the description of Charles Darwin’s frog as Rana charlesdarwini in 1998, its generic placement has been a taxonomic enigma. Subsequent studies first transferred this species to the dicroglossid genus Limnonectes, and then considered it as a ceratobatrachid of the genus Ingerana, which has since been moved to the family Dicroglossidae. However, recent works have doubted this generic placement and also suggested the possibility of its sister relationship with the genus Liurana, within Ceratobatrachidae. Nonetheless, there have been no detailed investigations to ascertain the generic placement of this taxon by confirming its phylogenetic position or using integrative taxonomic approaches. Here, we provide the first molecular assessment of Ingerana charlesdarwini based on mitochondrial and nuclear DNA and reveal that it is nested in the dicroglossid genus Minervarya. A member of the Minervarya anda- manensis species group, Minervarya charlesdarwini comb. nov. is sister taxon to M. andamanensis and shows relatively shallow ge- netic distances (2.8–3.6%) in the 16S gene. Both species are widely distributed, occur sympatrically, and exhibit high morphological variations, leading to long-standing confusions with other dicroglossid frogs reported from the region. Our combined morphological and molecular studies on dicroglossid frogs sampled across the known ranges of these species suggest that reports of Limnonectes doriae (Boulenger, 1887) and L. hascheanus (Stoliczka, 1870) from the Andamans are misidentifications of the former two, pointing to the absence of genus Limnonectes from the Andaman Islands. Our study also reveals the novel record of Minervarya agricola from the Andamans, a species that appears to have been confused with Fejervarya limnocharis and Minervarya keralensis in the literature and misidentified museum specimens, and is found to be widely distributed across these islands. We further find another congener from the Nicobar group of Islands, M. nicobariensis, to be closely related to M. charlesdarwini. Similar to the case of Andaman dicroglossids, our work emphasises on the need for further studies to ascertain the taxonomic identities and generic placement of Minervarya and Limnonectes species reported from the Nicobars